Two Approaches to Examine the Impact of Different Credit Default Indicators on Real Estate Loans - Pfalz Reimar (Baltic Journal of Real Estate Economics and Construction Management, 2019)
Financing of real estates was a trigger of the largest financial crisis after the “Great Depression” from the early thirties in the last century. One of the main causes of this 2007 crisis was poor risk management in real estate financing. The aim of this paper is to examine the impact of different classes of indicators on credit default rates of real estate loans. Two research approaches should confirm a model that proves how strong the relationship is between different predictor variables such as interest rates, macroeconomic and individual indicators on the response variable of credit defaults. The first approach focuses on conducting descriptive and inferential experimental research by collecting secondary data in different markets and by analysing these data for correlations and linear regressions. The second approach is an expert survey of different banks to compare and complement the results of the first research approach. The research provides the evidence that individual indicators and macroeconomic indicators have a higher impact on credit defaults than interest rates. The scientific research on this theme has led to nearly the same results in different markets: the unemployment rate and thus personal conditions are the most responsible predictors for the credit defaults, also in different markets. The novelty of the present research is the proof that a banking survey with primary data on the causes of credit defaults confirms and complements the results of the secondary data analysis.